Antenatal Synthetic Glucocorticoid Exposure at Human Therapeutic Equivalent Doses Predisposes Middle-Age Male Offspring Baboons to an Obese Phenotype That Emerges With Aging. (May 2019) - Huber, Hillary F.; Kuo, Anderson H.; Li, Cun; Jenkins, Susan L.; Gerow, Kenneth G.; Clarke, Geoffrey D.; Nathanielsz, Peter W.
Introduction: Women threatening premature delivery receive synthetic glucocorticoids (sGC) to accelerate fetal lung maturation, reducing neonatal mortality and morbidity. Few investigations have explored potential long-term offspring side effects. We previously reported increased pericardial fat and liver lipids in 10-year-old (human equivalent 40 years) male baboons exposed to 3 antenatal sGC courses. We hypothesized middle-aged sGC male offspring show obesity-related morphometric changes. Methods: Pregnant baboons received courses of 2 betamethasone injections (175 μg·kg −1 ·d −1 intramuscular) at 0.6, 0.64, and 0.68 gestation. At 10 to 12.5 years, we measured morphometrics and serum lipids in 5 sGC-exposed males and 10 age-matched controls. We determined whether morphometric parameters predicted amount of pericardial fat or lipids. Life-course serum lipids were measured in 25 males (7-23 years) providing normal regression formulas to compare sGC baboons' lipid biological and chronological age. Results: Birth weights were similar. When studied, sGC-exposed males showed a steeper weight increase from 8 to 12 years and had increased waist and hip circumferences, neck and triceps skinfolds, and total and low-density lipoprotein cholesterol. Triceps skinfold correlated with apical and midventricular pericardial fat thickness, hip and waist circumferences with insulin. Conclusions: Triceps skinfold and waist and hip circumferences are useful biomarkers for identifying individuals at risk for obesity and metabolic dysregulation following fetal sGC exposure. Prenatal sGC exposure predisposes male offspring to internal adiposity, greater body size, and increased serum lipids. Results provide further evidence for developmental programming by fetal sGC exposure and call attention to potential emergence of adverse life-course effects.